Selected Problems of Generating Apposition Groups in Old Polish - Zbróg, Piotr (Respectus Philologicus, 2020)
The subject of interest in this chapter is the concepts of creating apposition groups that appear in the literature on the subject, e.g. zbawiciel Jesus, dziewica Maryja, matka jego, słudze Bryjidzie. Opposing theories on this topic indicated on the one hand that apposition was an element added to the parent unit, and on the other hand, that apposition was the effect of transforming the deep structure into surface constructs. These approaches were, usually intuitive, reflected by language courts describing the title expressions since the beginning of the 19th century. In this study, they were traced and proved the dominance of opinions about the syntactic starting point in the derivative of apposition. In addition, other aspects of the characteristics of the groups of positions are discussed, placing them in the basic dichotomy of the derivation of positions.